Remarks at Srebrenica Commemoration, Srebrenica, Bosnia and Herzegovina, July 11, 2005 - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, remembers and honors the victims and the survivors of the worst act of genocide in Europe since the World War II and commits to helping rebuild shattered lives. He resolves that these horrible events must never be repeated. The World Bank has been able to participate in building a better future for Bosnia and he appeals to everyone to stand together to make the dreams of the young generation a reality.